Influencia de la política en la Prensa Radial del Casco Central, Cantón Buena Fe año 2019 - Cedeño Tapia, Tamara Alejandra (2020)
The radio press emerged on almost the entire planet as a reaction to the monopolies of the industry and initially identified itself as "free radio", often broadcast underground, under the term "pirate." Today it is a widely used model in Latin America, which offers new forms of expression, even if it is a practice immersed in consolidation processes and, even, recognition of the legislative and governmental authorities of each country. The technological development of communications has led us to live a media culture, both in social relationships and in politics. The communication and information systems have privileged the media, this actually makes communication problems fundamentally respond to specific interests of sectors of political and economic power. Ecuador currently has a communication law that has allowed certain media to manipulate information, to the point that some journalists have abused, blackmailed and even dishonored ordinary and public citizens, persuading their objectives to deliver economic benefits to stop this information. Local radio media that enjoy popularity and acceptance have also been objects of criticism not only of the political powers but of the common citizen who states that some radio media lend themselves to make information a political circus.